KEBIJAKAN PENGATURAN PERIMBANGAN KEUANGAN DALAM KONSEPSI DAN PERSPEKTIF KEADILAN - Wijaya, I Putu; Astariyani, Ni Luh Gede (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014, 2014)
Indonesia has the basic rules regarding the financial balance between central governments and local governments which are regulated in Law No. 33 year 2004 . There are problems that the want financial balance between central government and local governments in the conception and justice perspectives . Writing method used is the method of normative research. The conclusion is the conception of justice lies in the latter last principle , namely the principle of separation between the good and the bad , for the first four principles are contradicts always at odds , so that the determining balance of justice is a principle in the final . In the perspective of fairness , financial balance attentied theory of justice, should be applied to all areas with the same percentage of income for the entire sector , so there is no area feels discriminated because it is the allocation of funds based on the income from natural resources in the region, so thus achieved social justice for all Indonesian people.
Keywords: Fiscal Balance , Conception of Justice , Justice Perspective